2001
DOI: 10.1046/j.1364-727x.2001.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk source on the rheological properties of yogurt during the gelation process

Abstract: This paper presents research on the effect of milk source on the rheological properties of curd during the gelation process of yogurt. The highest value for viscosity was exhibited by ovine milk, followed by caprine, bovine and camel milks. For bovine, ovine and caprine milk, three different transient viscosity stages were identified and described by mathematical expressions, whereas camel milk showed no significant variation in viscosity during gelation. The chemical composition of milk, namely total solids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 13 publications
2
32
0
3
Order By: Relevance
“…Physicochemical properties of camel and cow milk showed that dry matter, protein and fat contents of camel milk (108.30 ± 10.74, 27.32 ± 0.06 and 34.50 ± 0.50 g L -1 , respectively) were lower than those of cow milk (120.50 ± 1.45, 33.75 ± 0.16 and 37.50 ± 0.71 g L -1 , respectively), in agreement with others (Al Haj and Al Kanhal 2010; Hailu et al 2016;Jumah et al 2001).…”
Section: Physicochemical Parameters Of Camel and Cow Milksupporting
confidence: 79%
See 1 more Smart Citation
“…Physicochemical properties of camel and cow milk showed that dry matter, protein and fat contents of camel milk (108.30 ± 10.74, 27.32 ± 0.06 and 34.50 ± 0.50 g L -1 , respectively) were lower than those of cow milk (120.50 ± 1.45, 33.75 ± 0.16 and 37.50 ± 0.71 g L -1 , respectively), in agreement with others (Al Haj and Al Kanhal 2010; Hailu et al 2016;Jumah et al 2001).…”
Section: Physicochemical Parameters Of Camel and Cow Milksupporting
confidence: 79%
“…In fact, the low contents of dry matter, protein and fat in camel milk compared with cow milk induced some modifications in the gelation properties. In this context, Jumah et al (2001) reported that the lower levels of dry matter and protein of camel milk, the weaker acid-induced gel. This could be explained by the fact that: (1) the lower fat content of camel milk induced the formation of a weak gel since fat globules could interact with the protein matrix improving the firmness of recombined milk gels (El Zubeir and Jabreel 2008;Lucey et al 1998b); and/or (2) the larger size of camel casein micelles affect the rheological properties of milk gels (Glantz et al 2010), in agreement with the results obtained in Fig.…”
Section: Size Distribution Of Casein Micellesmentioning
confidence: 99%
“…www.ital.sp.gov.br/bj fermentados de cabra, ovelha (JUMAH et al, 2001;PARK, 2007), vaca e camela (JUMAH et al, 2001) (2000), Vinderola e Reinheimer (2000) e Bonczar et al (2002) para iogurtes probióticos, iogurtes, produtos lácteos fermentados e iogurtes de leite de ovelha, respectivamente. Este comportamento, também observado no presente trabalho, poderia ter sido em decorrência do uso do soro em substituição ao leite.…”
Section: Cunha T M Et Alunclassified
“…On the contrary, Tarakçı 29 found that the viscosity values of yogurt samples decreased during storage period. The effect of different types of milks on viscosity and incubation time was studied by Jumah et al 30 . They found that sheep milk reached the highest viscosity value, followed by caprine and bovine milk.…”
Section: Syneresis and Viscositymentioning
confidence: 99%